Psychosocial problems of children from alcoholic families. - Ślaski, Sławomir (Studia Psychologica: Theoria et praxis, 2004)
The author reviews a current literature on children who are brought up by families with alcoholic problem. The analysis concentrate on 4 groups of the problems: on discovering the kinds of conflicts which children from alcoholic families experience, on researching factors which could determinate probabilities of psychopathology, on prenatal research, and on psychoactive substance abuse by children from alcoholic families.